Repurposing Potential of the Antiparasitic Agent Ivermectin for the Treatment and/or Prophylaxis of COVID-19 - Hoda Awad; Basmala Hassan; Sara Dweek; Yasmeen Aboelata; Mutasem Rawas-Qalaji; Iman Saad Ahmed (MDPI AG, 2022)
Due to the rapid, vast, and emerging global spread of the Coronavirus Disease 2019 (COVID-19) pandemic, many drugs were quickly repurposed in a desperate attempt to unveil a miracle drug. Ivermectin (IVM), an antiparasitic macrocyclic lactone, was tested and confirmed for its in vitro antiviral activity against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in early 2020. Along with its potential antiviral activity, the affordability and availability of IVM resulted in a wide public interest. Across the world, trials have put IVM to test for both the treatment and prophylaxis of COVID-19, as well as its potential role in combination therapy. Additionally, the targeted delivery of IVM was studied in animals and COVID-19 patients. Through this conducted literature review, the potential value and effectiveness of the repurposed antiparasitic agent in the ongoing global emergency were summarized. The reviewed trials suggested a value of IVM as a treatment in mild COVID-19 cases, though the benefit was not extensive. On the other hand, IVM efficacy as a prophylactic agent was more evident and widely reported. In the most recent trials, novel nasal formulations of IVM were explored with the hope of an improved optimized effect.